2004
DOI: 10.2174/1568010043343903
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Necrosis Factor-α in the Therapy of Psoriasis

Abstract: Tumor necrosis factor-alpha (TNF-alpha) plays a fundamental role in the initiation and persistence of skin inflammation in psoriasis. The best evidence of the essential activity of this cytokine in the pathogenesis of psoriasis came from the observation that selective TNF-alpha blockers are dramatically effective in the therapy of this disease. The TNF-alpha inhibitors, infliximab and etanercept, have been employed with success in moderate to severe psoriasis and in psoriatic arthritis in randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…TNF-α can be produced by many cell types, including activated monocytes, macrophages, neutrophils, mast cells, dendritic cells, endothelial cells and different T cell subsets. 1 When released from activated cells, this ubiquitous cytokine is capable of stimulating the production of other pro-inflammatory molecules such as interleukins (IL-1, IL-6, IL-8, nuclear transcription factor KB) and adhesion molecules such as ICAM-1, P-selectin and E-selectin 7 and together with these agents, TNF-α can be viewed as a key driver and initiator of cytokine cascades that result in major, chronic inflammation and tissue damage.…”
Section: Pivotal Role Of Tnf-α In Inflammatory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α can be produced by many cell types, including activated monocytes, macrophages, neutrophils, mast cells, dendritic cells, endothelial cells and different T cell subsets. 1 When released from activated cells, this ubiquitous cytokine is capable of stimulating the production of other pro-inflammatory molecules such as interleukins (IL-1, IL-6, IL-8, nuclear transcription factor KB) and adhesion molecules such as ICAM-1, P-selectin and E-selectin 7 and together with these agents, TNF-α can be viewed as a key driver and initiator of cytokine cascades that result in major, chronic inflammation and tissue damage.…”
Section: Pivotal Role Of Tnf-α In Inflammatory Diseasesmentioning
confidence: 99%
“…After initial proof of concept, safety and tolerability studies, this novel class of drugs, which currently includes among a growing list of entities, infliximab, etanercept, efalizumab, alefacept, onercept and adalimumab, has been studied in a wide array of inflammatory conditions. 1,8 In the management of rheumatoid arthritis, clinical studies of anti-TNF drugs used alone or in combination with methotrexate have shown consistent improvement in signs and symptoms of disease as well as patient function, with a dramatic D I S E A S E M A N A G E M E N T a n t i -T N F t h e r a p i e s slowing of radiographic damage, such that anti-TNF agents combined with optimal doses of methotrexate are currently considered the best therapeutic regimen for patients who fail to respond adequately to traditional diseasemodifying drugs. 10 Investigation of the therapeutic potential of anti-TNF drugs has to consider their efficacy and safety in equal measure.…”
Section: The Development Of Targeted Anti-tnf Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two agents are currently utilized in the treatment of AS, infliximab and etanercept, and openlabel trials have demonstrated the efficacy and safety of both these drugs [19,20]. Patients treated with etanercept showed an improvement in the Bath Ankylosing Spondylitis Disease Activity Index ‡ 50% [18]. Furthermore, other open-label trials have demonstrated the efficacy and safety of TNF-a inhibitors for the treatment of Ps and PsA [21][22][23].…”
mentioning
confidence: 99%
“…Although TNF-a inhibitors were first developed for patients with RA, they were subsequently also approved for the use in patients with AS. The increased expression of TNF-a in serum and at the sacroiliac joints in patients with AS and the close immunological relationship between spondyloarthropathies and CD were the main reason to consider TNF-a inhibitors as a new therapeutic option for these patients [18,19]. Two agents are currently utilized in the treatment of AS, infliximab and etanercept, and openlabel trials have demonstrated the efficacy and safety of both these drugs [19,20].…”
mentioning
confidence: 99%